Semiotical Interpretation of Romance in Joko Pinurbo's Poetry: A Peircean Analysis - Audri Israh Muslimah; Samsiarni; Emil Septia (Jurnal Bebasan, 2024)
This study aims to describe the semiotic meaning (index) in depicting romance in the poetry of Joko Pinurbo, using Charles Sanders Peirce's semiotic theory. The research employs a content analysis method, with data drawn from a selection of Joko Pinurbo's poems, including "Sebelum Memasuki," "Sungai Kecil," "Menyambut Tahun Baru," "Jalan Korona," "Tangga Tinggi," "Tidur Nyenyak," "Maut Tersenyum," "Elegi, 2020," "Solilokui Sebelum Buruk," "Bakso Lezat," and "Di Meja Makan.". The technique used for data collection is reading and note-taking. The analysis of index signs within Joko Pinurbo's poems reveals six different romantic expressions, each highlighted through semiotic indices. The findings emphasize the interpretation of these indexical signs to uncover the romantic currents that flow throughout the poems. This research provides a comprehensive understanding of how index signs can be utilized to analyze the romantic themes present in Joko Pinurbo's poetic works, contributing to the broader field of semiotic studies and literary interpretation.